Episodi di mortalità in storioni (Acipenser spp.) d’allevamento - Prearo M.; Giorgi I.; Marturano S.; Gasparri F.; Arsieni P.; FIORAVANTI, MARIALETIZIA; ZANONI, RENATO GIULIO (s.n, 2008)
During 2004-spring 2008, 21 bacterial outbreaks in farmed Siberian sturgeon (Acipenser baeri), 3 in Russian sturgeon (A. gueldenstaedti) and 2 in hydrid sturgeons with different mortality, were reported in Northern Italy. The bacterial infections isolated were caused by Aeromonas hydrophila (12 cases), Pseudomonas fluorescens (7 cases), A. sobria (5 cases), Plesiomonas shigelloides (1 case) and Photobacterium damselae subsp. damselae (1 case). In all cases, the characteristic symptoms were the presence of hemorrhagic enteritis in the terminal tract of the intestine.